Cannabis-assisted psychotherapy for complex dissociative posttraumatic stress disorder: A case report - Ragnhildstveit, Anya; Kaiyo, Miriam; Snyder, Matthew Brian; Jackson, Laura Kate; Lopez, Alex; Mayo, Chasity; Miranda, Alyssa Claire; August, River Jude; Seli, Paul; Robison, Reid; Averill, Lynnette Astrid (Frontiers in Psychiatry, 2023)
Background: A dissociative subtype of posttraumatic stress disorder, known as ‘D-PTSD’, has been included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. In addition to meeting criteria for PTSD, patients endorse prominent dissociative symptoms, namely depersonalization and derealization, or detachment from one’s self and surroundings. At present, this population is supported by a highly heterogeneous and undeveloped literature. Targeted interventions are therefore lacking, and those indicated for PTSD are limited by poor efficacy, delayed onset of action, and low patient engagement. Here, we introduce cannabis-assisted psychotherapy (CAP) as a novel treatment for D-PTSD, drawing parallels to psychedelic therapy. Case Presentation: A 28-year-old female presented with complex D-PTSD. In a naturalistic setting, she underwent 10 sessions of CAP, scheduled twice monthly over five months, coupled with integrative cognitive behavioral therapy. An autonomic and relational approach was leveraged, specifically psychedelic somatic interactional psychotherapy. Acute effects included oceanic boundlessness, ego dissolution, and emotional breakthrough. From baseline to post-treatment, the patient showed a 98.5% reduction in pathological dissociation, as measured by the Multidimensional Inventory of Dissociation, no longer meeting criteria for D-PTSD. This was accompanied by decreased cognitive distractibility and emotional suffering, as well as increased psychosocial functioning. The patient has sustained improvements for over two years to date. Conclusions: There is urgency to identify treatments for D-PTSD. The present case, while inherently limited, underscores the potential of CAP as a therapeutic option, leading to robust and sustained improvement. Subjective effects were comparable to those produced by classic and non-classic psychedelics, such as psilocybin and ketamine. Further research is warranted to explore, establish, and optimize CAP in D-PTSD, and to characterize its role in the pharmacological landscape.